A religiosidade grega e a tragédia ática no jovem Nietzsche (1869-1875) - Dantas, Camilo de Jesus (2018)
This final paper approaches the relation between Greek religiosity, and the Attica tragedy in the final stage of Friedrich Nietzsche’s thinking and it intends to explain the relevance of the religion within the Hellenic cultural development process. It intends, from Nietzsche’s writings during the years of 1869 to 1875, handled by interpreters, Hellenists and old Greek texts, to achieve a clearer comprehension as religion, from which soil the Greek art has come, in a special way the tragedy. It is, therefore, an investigation of how in the light of the young Nietzsche´s Philosophy would have been articulated religiosity and art in ancient Greece